1999
DOI: 10.1088/0953-8984/11/18/310
|View full text |Cite
|
Sign up to set email alerts
|

Chemical exchange in NH4HSeO4single crystals studied by two-dimensional2H nuclear magnetic resonance

Abstract: Processes of chemical exchange of deuterons in partially deuterated ammonium hydrogen selenate, NH4HSeO4 (AHSe), crystals are investigated by means of 2H nuclear magnetic resonance (NMR) experiments over a wide temperature range. The temperature dependencies of the quadrupole line splittings in the one-dimensional spectra of AHSe above 350 K revealed line-shape changes which are characteristic for chemical exchange processes. A detailed study of these exchange processes in AHSe is achieved by means of two-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Such crystals serve as very appropriate model objects in order to verify the various assumptions about the microscopic mechanisms of ionic conductivity. Our 2-D-2H-NMR (nuclear magnetic resonance) exchange spectroscopy experiments [5][6][7] prove the presence of chemical exchange processes between deuterons of hydrogen bonds in the structure of ammonium hydrogen selenate NH4HSeO 4 (AHSe), betaine phosphate (BP), betaine phosphite (BPI) and mixed crystals BPI_xBPIx, containing quasi 1-D chains of SeO4-, PO4-, or PO3-tetrahedra connected by hydrogen bonds. A close relationship between chemical exchange and ionic conductivity processes was proved [7].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Such crystals serve as very appropriate model objects in order to verify the various assumptions about the microscopic mechanisms of ionic conductivity. Our 2-D-2H-NMR (nuclear magnetic resonance) exchange spectroscopy experiments [5][6][7] prove the presence of chemical exchange processes between deuterons of hydrogen bonds in the structure of ammonium hydrogen selenate NH4HSeO 4 (AHSe), betaine phosphate (BP), betaine phosphite (BPI) and mixed crystals BPI_xBPIx, containing quasi 1-D chains of SeO4-, PO4-, or PO3-tetrahedra connected by hydrogen bonds. A close relationship between chemical exchange and ionic conductivity processes was proved [7].…”
Section: Introductionmentioning
confidence: 95%
“…This is caused on the one hand by the important practical applications of these crystals in energy storage and fuel cells and on the other hand by the possibility to study the fundamental problem of the microscopic mechanism of the electric conductivity ha superionic crystals [1][2][3][4][5][6]. From this point of view of particular interest are crystals with the structural peculiarity of quasi one-dimensional (l-D) chains of atomic groups bound by hydrogen bonds showing proton conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal then transits to the incommensurate phase (III) at 261 K (=T i ) and to the ferroelectric phase (IV) at 250 K (=T C1 ). When the temperature drops below 98 K (=T C2 ), the crystal commences its low temperature phase and becomes non-ferroelectric [12][13][14]. Previous studies of NH 4 HSeO 4 with 1 H nuclear magnetic resonance (NMR) spectra, nuclear spin-spin relaxation times T 2 , in the laboratory frame and conductivity measurements in the vicinity of T SI concluded that the diffusions of protons and NH 4 + cations in the crystals were isotropic [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of NH 4 HSeO 4 with 1 H nuclear magnetic resonance (NMR) spectra, nuclear spin-spin relaxation times T 2 , in the laboratory frame and conductivity measurements in the vicinity of T SI concluded that the diffusions of protons and NH 4 + cations in the crystals were isotropic [15,16]. In addition, the microscopic mechanism of deuteron transport in ND 4 DSeO 4 crystals was studied by means of 2 H NMR [13,[17][18][19]. A detailed analysis of the behavior of the ammonium and HSeO 4 deuterons in ND 4 DSeO 4 was discussed by Ivanov et al [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation